Cytotoxic effect of ethanol extract of microalga, Chaetoceros calcitrans, and its mechanisms in inducing apoptosis in human breast cancer cell line - Nigjeh, Siyamak Ebrahimi; Md. Yusoff, Fatimah; Mohammed Alitheen, Noorjahan Banu; Pirozyan, Mehdi Rasoli; Yeap, Swee Keong; Omar, Abdul Rahman (Hindawi Publishing Corporation, 2013)
Marine microalgae have been prominently featured in cancer research. Here, we examined cytotoxic effect and apoptosis mechanism of crude ethanol extracts of an indigenous microalga, Chaetoceros calcitrans (UPMAAHU10) on human breast cell lines. MCF-7 was more sensitive than MCF-10A with IC50 value of 3.00±0.65, whilst the IC50 value of Tamoxifen against MCF-7 was 12.00±0.52 g/mL after 24 hour incubation. Based on Annexin V/Propidium iodide and cell cycle flow cytometry analysis, it was found that inhibition of cell growth by EEC on MCF-7 cells was through the induction of apoptosis without cell cycle arrest. The apoptotic cells at subG0/G1 phase in treated MCF-7 cells at 48 and 72 hours showed 34 and 16 folds increased compared to extract treated MCF-10A cells which showed only 6 and 7 folds increased at the same time points, respectively. Based on GeXP study, EEC induced apoptosis on MCF-7 cells via modulation of CDK2, MDM2, p21Cip1, Cyclin A2, Bax and Bcl-2. The EEC treated MCF-7 cells also showed an increase in Bax/Bcl-2 ratio that in turn activated the caspase-dependent pathways by activating caspase 7. Thus, marine microalga, Chaetoceros calcitrans may be considered a good candidate to be developed as a new anti-breast cancer drug.